Auriculotherapy for Labour Pain Management: a Systematic Review and Meta-Analysis - Velan Arumugam; Arthi Balakrishnan; V. Venugopal; Poonguzhali S; Gayathri Annamalai; Prabu Narasimman; S. T. Venkateswaran; Maheshkumar Kuppusamy (Medical Association of Pharmacopuncture Institute, 2024)
Importance: Labor pain presents significant challenges during childbirth, necessitating effective pain management strategies. Auriculotherapy, a non-pharmacological intervention targeting specific ear points, has been explored as a potential solution for alleviating labor pain. Objective: This systematic review and meta-analysis aimed to evaluate the efficacy of auriculotherapy in reducing labor pain intensity and improving maternal satisfaction. Data Resources: The electronic databases PubMed, Scopus, ScienceDirect, and Cochrane Library were searched from inception until December 2023 for randomized controlled trials (RCTs) investigating auriculotherapy as an intervention for labor pain management. Study Selection: Two authors independently conducted literature selection based on predefined criteria (i.e., RCTs assessing auriculotherapy for labor pain management). Data Extraction and Synthesis: Data extraction was performed independently by two authors, and a random-effects model was used for meta-analysis. The pooled mean difference (MD), with a 95% confidence interval (CI), was calculated to estimate the effect size. Main Outcome(s) and Measure(s): The primary outcome was labor pain intensity measured on the visual analog scale. Results: Meta-analysis of five RCTs involving 451 patients revealed a significant reduction in labor pain following auriculotherapy compared with no treatment (MD, -1.78; 95% CI, -2.62 to -0.93). However, significant heterogeneity was observed among the included studies (I2, 87%; p < 0.01). Conclusions and Relevance: Despite the observed heterogeneity, this meta-analysis suggests that auriculotherapy holds promise as a non-pharmacological intervention for alleviating labor pain. Further investigation is warranted to refine auriculotherapy protocols and assess its long-term effects, thereby enhancing its potential as a viable option for labor pain management.